Ma’āni Alfādz “ al- Insān” Wa Muradifuha Fi Qāmus al araby – al Indunisy Ta’lif Mahmud Yunus - Nela Salsabilah; Isniyatun Niswah (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2024)
This research discusses the meaning of the word "human" and its synonyms in the Arabic-Indonesian dictionary by Mahmud Yunus. This research aims to analyze the meaning of the word "human" and its synonyms, as well as the role of different words in Arabic language education. This research uses a qualitative approach, where the type of research is literature study, namely using a data collection method based on a study of books, literature, notes and scientific works related to this research. The results of this research show that synonyms in Arabic language teaching and learning are not just different words that have one meaning, but understanding the meaning of these words also has its own purpose, such as discussing the meaning of the words “human” and its synonyms. The synonyms contained in the Arabic Dictionary by Mahmud Yunus are: Basyar, Naas, Insan, and Bani Adam.